Does Source of Foreign Direct Investment Matter for Nigeria’s Economic Growth? - Uwajumogu, Nkechinyere; Ojike, Richard O.; Ogbonna, Innocent C. (International Journal of Economics and Financial Issues, 2018)
Foreign Direct Investment (FDI) is one of the sources used as a wedge to bridge the saving-financial requirement gap and many policies and programmes are mapped out to attract FDI in Nigeria. The study was aimed at examining whether source of FDI matter for growth in Nigeria. Using Autoregressive Distributed Lag (ARDL) bound test model, we disaggregated FDI sources to determine individual impact, and then add interest rate and exchange rate to capture macroeconomic conditions of the economy. The results show while inflow from Asian and African countries had significant and positive impact on GDP growth rate, FDI from USA and EU countries had the opposite effect. Therefore, the impacts of FDI indeed differs depending on the country of origin and this is caused by differences in market structures of host country and country of origin, business system, institutions, policy formulation process, organizational features, level of development etc. Keywords: Foreign Direct Investment; Autoregressive Distributed Lag; Source country; host country JEL Classifications: F6, O2, O4 DOI: https://doi.org/10.32479/ijefi.6862